2019
DOI: 10.3389/fpls.2019.00007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Dehydrin Accumulation and Winter Survival in Winter Wheat and Barley Grown in the Field

Abstract: Low temperatures represent a crucial environmental factor determining winter survival (WS) of barley and wheat winter-type varieties. In laboratory experiments, low temperatures induce an active plant acclimation response, which is associated with an enhanced accumulation of several stress-inducible proteins including dehydrins. Here, dehydrin accumulations in sampled wheat (WCS120 protein family, or WCS120 and WDHN13 transcripts) and barley (DHN5 protein) varieties grown in two locations for two winters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…The studied COR/LEA (WCS120, WCOR410, WCOR14) transcript levels decreased throughout winter except for WCOR14 transcript in winter Manitou; however, significant alterations among the different seasons were observed which corresponded with fluctuations in soil temperature at crown depth. In contrast, in maritime and transitional zones such as Italy or Czechia where freezing periods are interspersed by relatively long periods of above-zero temperatures during winter (freeze-thaw cycles) when partial cold deacclimation occurs, relatively low levels of COR/LEA/dehydrin proteins were found in plant tissues in later phasesof winter (January, February) and these levels did not correspond with the plant freezing tolerance[29,67] since plants are already vernalized at this time and cannot efficiently re-acclimate after a period of deacclimation.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…The studied COR/LEA (WCS120, WCOR410, WCOR14) transcript levels decreased throughout winter except for WCOR14 transcript in winter Manitou; however, significant alterations among the different seasons were observed which corresponded with fluctuations in soil temperature at crown depth. In contrast, in maritime and transitional zones such as Italy or Czechia where freezing periods are interspersed by relatively long periods of above-zero temperatures during winter (freeze-thaw cycles) when partial cold deacclimation occurs, relatively low levels of COR/LEA/dehydrin proteins were found in plant tissues in later phasesof winter (January, February) and these levels did not correspond with the plant freezing tolerance[29,67] since plants are already vernalized at this time and cannot efficiently re-acclimate after a period of deacclimation.…”
mentioning
confidence: 92%
“…Due to versatility in their structure responding to cell hydration status, dehydrins can adopt multiple molecular functions corresponding to cell hydration status and interaction partners which include not only proteins but also membrane surfaces [15,16]. Studies dealing with dehydrin molecular functions under cold reported their chaperone, cryoprotective, antifreeze, ion-binding and radical scavenging functions for some cold-responsive dehydrins [14,19]; for more details on dehydrin molecular structure and functions, see Kosová et al (2019) [20]. In winter wheat and barley plants, the major cold-inducible dehydrins belong to Kn structural group harboring multiple K-segments in their molecules (K6 in wheat WCS120 while K9 in barley DHN5) and revealing significant cryoprotective activities [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, studies in plants have shown that qualitative or quantitative changes which some marker proteins undergo in response to stress reveal a correlation with the degree of stress tolerance. As an example, our studies on Kn-type dehydrins reveal a correlation between the relative abundance of the proteins and acquired frost tolerance expressed as the lethal temperature for 50% of the sample (LT50) in winter wheat and barley cultivars subjected to cold acclimation treatment (Kosová et al , 2008, 2013; Vítámvás et al , 2010, 2019). However, as with other quantitative traits, the quantitative changes in relative abundance of marker proteins are determined by G×E interactions which limit their application in breeding programmes.…”
mentioning
confidence: 93%